Philosophizing About Entrepreneurship: Introducing Entrepreneurship Through the Debate of Fundamental Questions. (23rd September 2022) - Allen, Jonathan P.
Debate is an active learning tool used across many disciplines. We report on the use of debates in an introductory Masters' level entrepreneurship course as a learning innovation, both face-to-face and online. Based on McBride's definition of the philosophy of entrepreneurship, the debates focus on fundamental questions in entrepreneurship research and thought. Rotating teams debate in front of their classmates, with the audience evaluating their debate performance immediately afterwards during a short debriefing led by the instructor. For half of the debates, teams are able to choose which side of argument to take, but for the other half they might be forced to defend positions that they believe are weaker or incorrect. The debate format embraces active learning theories, requiring both speakers and audience to make choices and evaluate peer-reviewed evidence, with an intent to develop higher-order critical thinking skills. We discuss the self-reported effects that entrepreneurial debates have on self-efficacy, moving from intention to action, and on the creation of memorable entrepreneurial events for this specific audience.